2008
DOI: 10.1016/j.cell.2008.09.043
|View full text |Cite
|
Sign up to set email alerts
|

Rac Activation and Inactivation Control Plasticity of Tumor Cell Movement

Abstract: Tumor cells exhibit two different modes of individual cell movement. Mesenchymal-type movement is characterized by an elongated cellular morphology and requires extracellular proteolysis. In amoeboid movement, cells have a rounded morphology, are less dependent on proteases, and require high Rho-kinase signaling to drive elevated levels of actomyosin contractility. These two modes of cell movement are interconvertible. We show that mesenchymal-type movement in melanoma cells is driven by activation of the GTPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

63
1,115
3
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 869 publications
(1,189 citation statements)
references
References 37 publications
63
1,115
3
8
Order By: Relevance
“…Rac GTPase activity critically regulates pseudopodial protrusions and mesenchymal cell migration in 3D gels (Sanz-Moreno et al, 2008;Friedl and Wolf, 2010), separately confirmed in the cell lines used in the present study by the use of dominant-negative Rac. Downstream from Rac, Arp2/3 initiates short-branched actin filaments that push against the cell membrane, leading to membrane protrusion.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Rac GTPase activity critically regulates pseudopodial protrusions and mesenchymal cell migration in 3D gels (Sanz-Moreno et al, 2008;Friedl and Wolf, 2010), separately confirmed in the cell lines used in the present study by the use of dominant-negative Rac. Downstream from Rac, Arp2/3 initiates short-branched actin filaments that push against the cell membrane, leading to membrane protrusion.…”
Section: Discussionsupporting
confidence: 77%
“…Videos were then converted to MPEG-4 files using Total video converter (OJOsoft, www.ojosoft.com). Cell invasion assays were adapted from a previously described method (Sanz-Moreno et al, 2008). Approximately 2.5 Â 10 4 cells were seeded within 1.7 mg/ml collagen gel containing o1% serum in 96-well flat bottom plates (100 ml of gel per well).…”
Section: Migration Analysismentioning
confidence: 99%
See 3 more Smart Citations